On the powers of powerful knowledge. Issue 3 (19th December 2013) - Young, Michael; Muller, Johan
Abstract The aim of this paper is to explore and clarify the idea of 'powerful knowledge' as a sociological concept and as a curriculum principle. The paper seeks to clarify its conceptual basis and to make its meaning and the arguments it implies, less ambiguous and less open to misunderstanding. This will enable us to suggest some of the research and policy options that it opens up. The paper begins with a brief discussion of the origins of the contemporary usage of the concept in the sociology of education and its explains its roots in the often neglected sociology of knowledge of Emile Durkheim. We draw from Durkheim the idea that 'powerful knowledge' is differentiated and specialised knowledge and trace this argument through the work of Vygotsky and, in more detail, of Basil Bernstein. Following Bernstein's analysis of the different forms that specialised knowledge can take, we consider the curriculum implications of the view that some forms, the STEM(Science, Technology, Engineering and Mathematics) subjects, are 'intrinsically more powerful than others'. We indicate the limits of this argument and in the final section suggest how the idea of powerful knowledge can be more broadly conceived to include the arts and humanities.